Pengaruh Kualitas Produk, Harga Dan Promosi Speaker Box Rhyme Terhadap Volume Penjualan Pada CV. Sinar Baja Eletric Di Surabaya Ely - Ely Julianus Tiballa; Bambang Karnain; Sugiharto Sugiharto; Achmad Daengs GS; Harsono Teguh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to analyze the role of product quality, price and promotionon sales volume of CV. Sinar Baja Electric. Research conducted at CV. Sinar Baja Electric, researchers took quantitative research methods, while the methods used to collect and were interviews, observasion and documentation. The analysis that the authors use in the study is descriptice qualitative analysis, multiple linear regression analysis, validation analysis and reability testing. Proceeds from sales of Speaker Box Rhyme at CV. Sinar Baja Electrichas experienced a decline in the past 3 years, this is evidenced by the sales result in 2018 of 28 pcs, while in 2019 there were 13 pcs and in 2020 there were 6 pcs. Based on the result obtained from the questionnaire distributed to cconsmers CV. Sinar Baja Electric, in use study used one dependent variable, namely sales volume and three independent variable, namely product quality, price and promotion. The regression model obtained from the multiple linear regression test in thie study is Y = 2,032 + 0,184X1 + 0,680X2 + 0,090X3 + 0,427. In this study there is a multiple linear test, namely the analysis of the coefficient of determination (R²), in table 4.10 it can be shown that 57,3% increase in sales volume of Rhyme speakers is influenced by independent variable, namely product quality (X1), price (X2) and promotion (X3), while the remaining 42,7% is influenced by other variable not examined in thi study. And based on the results of the beta value in the multiple linear regression the in the table 4.9, it can be concluded that only the price variable has a significant effect on volume sales CV. Sinar Baja Electric with a value of 0,661 and the rest (product quality and promotion) has no significant effect on sales volume at CV. Sinar Baja Electric in Surabaya.